History of the Arrangement of Contempt of The President in Indonesia - Baiq Juli Nirtalina; Ade Sultan Mahmud; Adinda Mutia Gani; Dena Murdiawati (Faculty of Law, University of Mataram, 2019)
This research aimed to find out the existence history of the Article on the arrangement of contempt of the President or vice President in Indonesia from the old order (orde lama), new order (ordebaru) to reformation era. Type of this research is normative legal research under conceptual approach which studied literatures through library research. The collected materials were processed and analyzed qualitatively with deductive thinking method. Research result indicates that the regulation on contempt of the President and vice President in Orde Lama andOrdeBaru era were accordingly to the Dutch colonial era. The regulation was terminated in the reformation era through the decree of the Supreme Court No.013-022/PUU-IV/2006 since it considered contradict the constitution 1945 (UUD 1945). Furthermore, contempt of the President and vice President regulated under Article 207 KUHP or Article 310-312 in term of the President or vice President regarded as ordinary civilian excluded their privileges as the law and human rights guaranteed each citizen’s equation before the law.